Herbivore-Induced Changes in Cotton Modulates Reproductive Behavior in the Moth Spodoptera littoralis - Zakir, Ali; Khallaf, Mohammed A.; Hansson, Bill S.; Witzgall, Peter; Anderson, Peter (Frontiers in Ecology and Evolution, 2017)
Plants produce chemical defense compounds to resist herbivore attack either by repelling the herbivores or attracting natural enemies of the herbivores. We have previously shown that volatile compounds from cotton released in response to herbivory by conspecifics reduce oviposition in cotton leafworm moth Spodoptera littoralis. It remained, however, unclear whether herbivore-induced changes also affect moth pre-mating and mating behaviours. In this study we examined the effect of herbivore-induced changes in cotton on reproductive behaviours i.e., female calling, male attraction and investment, and mating behaviour in S. littoralis. We found a reduction in the number of females calling i.e., females releasing pheromone, in the presence of cotton plants damaged by larvae of S. littoralis compared to undamaged plants. Females also spent significantly less time calling and showed a delay in calling in the presence of damaged plants. Furthermore, males exhibited significantly delayed activation and reduced attraction towards female sex pheromone in the presence of damaged plants. We also found that mating success and the number of matings were significantly reduced in the presence of damaged plants whereas male investment i.e., spermatophore weight, was not affected. Thus, our study provides evidence that herbivory by conspecifics on host plants affect pre-mating and mating behaviours in an insect herbivore.